Relações poder central/poder local : a permanência de jurisdições senhoriais no Portugal Moderno : o estudo de um caso : Vila do Conde - Polónia, Amélia (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The present article intends to debate, in the context of Early Modern Portugal, the difficult relationships between royal power, going through a process of centralization and politicaladministrative reinforcement, and the permanence of a manorial structure typically medieval: the manor – lay or ecclesiastical. The study develops around a case study: that of Vila do Conde, in the 16th century, in order to examine the local implications of such dynamic, for the configuration of society and for the exercise of local power.